Situation Report: Romania, 3 February 1981 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Romania's Good-Neighborly Balkan Diplomacy New Law on Prices The 1981 State Budget New Negotiations for Canadian-Made Nuclear Reactors The Campaign to Improve Agricultural Activities Crime and the Romanian Socialist Economy Dissatisfaction with Youth's Education and Training Major Corruption Case Uncovered: Political Implications? Administrative Organization of the Country Improved